Research hotspots and frontiers of vagus nerve stimulation in stroke: a bibliometric analysis - Liu, Mingyue; Liu, Mengya; Zhang, Bohan; Fang, Mingzhu; Chen, Ke; Zhang, Yishen; Wang, Qian; Tian, Chunyan; Wu, Liang; Li, Zhe (Frontiers in Neuroscience, 2024)
BackgroundVagus nerve stimulation (VNS) has emerged as a promising therapeutic approach for stroke treatment, drawing significant attention due to its potential benefits. However, despite this growing interest, a systematic bibliometric analysis of the research landscape is yet to be conducted.MethodsWe performed a comprehensive search of the Web of Science Core Collection (WoSCC) database for literature published between January 1, 2005, and August 31, 2024. CiteSpace and the Bibliometrix package in R software were used to generate knowledge maps and conduct a bibliometric analysis. This analysis focused on publication output, geographic distribution, institutional involvement, author and co-cited author networks, journal and co-cited journal relationships, co-cited references, and keyword trends.ResultsDuring the study period, 316 publications on VNS in stroke were identified, authored by 1,631 researchers from 1,124 institutions across 172 countries or regions. The number of publications showed steady growth, with the United States of America (USA) leading as the primary contributor. The University of Texas System emerged as the most active research institution. Frontiers in Neuroscience published the highest number of articles, while Stroke had the most citations. Professor Michael P. Kilgard authored the largest number of papers and was also the most frequently cited researcher. The main research trends focus on investigating VNS mechanisms via animal models and exploring its application in improving post-stroke sensorimotor function in the upper limbs. Moreover, VNS is showing promise in enhancing non-motor functions, such as swallowing, speech, and cognition, while addressing complications like post-stroke insomnia, depression, and disruptions in gut microbiota.ConclusionThis bibliometric study offers a comprehensive overview of the research landscape and emerging trends in VNS for stroke rehabilitation, providing a solid foundation and reference point for future research directions in this field.